Endoplasmic Reticulum Stress Induces Different Molecular Structural Alterations in Human Dilated and Ischemic Cardiomyopathy - Ortega, Ana; Roselló-Lletí, Esther; Tarazón, Estefanía; Molina-Navarro, Maria Micaela; Martínez-Dolz, Luis; González-Juanatey, José Ramón; Lago, Francisca; Montoro-Mateos, Jose David; Salvador, Antonio; Rivera, Miguel; Portolés, Manuel (PloS one, 2014)
The endoplasmic reticulum (ER) is a multifunctional organelle responsible for the synthesis and folding of proteins as well as for signalling and calcium storage, that has been linked to the contraction-relaxation process. Perturbations of its homeostasis activate a stress response in diseases such as heart failure (HF). To elucidate the alterations in ER molecular components, we analyze the levels of ER stress and structure proteins in human dilated (DCM) and ischemic (ICM) cardiomyopathies, and its relationship with patient's functional status. We examined 52 explanted human hearts from DCM (n = 21) and ICM (n = 21) subjects and 10 non-failing hearts as controls. Our results showed specific changes in stress (IRE1, p<0.05; p-IRE1, p<0.05) and structural (Reticulon 1, p<0.01) protein levels. The stress proteins GRP78, XBP1 and ATF6 as well as the structural proteins RRBP1, kinectin, and Nogo A and B, were upregulated in both DCM and ICM patients. Immunofluorescence results were concordant with quantified Western blot levels. Moreover, we show a novel relationship between stress and structural proteins. RRBP1, involved in procollagen synthesis and remodeling, was related with left ventricular function. In the present study, we report the existence of alterations in ER stress response and shaping proteins. We show a plausible effect of the ER stress on ER structure in a suitable sample of DCM and ICM subjects. Patients with higher values of RRBP1 had worse left ventricular function.